2011
DOI: 10.1093/jrs/fer010
|View full text |Cite
|
Sign up to set email alerts
|

'It Would be Okay If They Came through the Proper Channels': Community Perceptions and Attitudes toward Asylum Seekers in Australia

Abstract: Australia's humanitarian programme contributes to UNHCR's global resettlement programme and enhances Australia's international humanitarian reputation. However, as the recent tragedy on Christmas Island has shown, the arrival of asylum seekers by boat continues to stimulate debate, discussion and reaction from the Australian public and the Australian media. In this study, we used a mixed methods community survey to understand community perceptions and attitudes relating to asylum seekers. We found that while p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
114
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(120 citation statements)
references
References 25 publications
5
114
0
1
Order By: Relevance
“…Such increases in racist incidents have coincided with a (failed) political attempt to amend/repeal Section 18C of the Racial Discrimination Act-a legislative protection from 'offensive behaviour because of race, colour or national or ethnic origin' (Racial Discrimination Act 1975, s.18C). Australia's formal humanitarian intake of asylum seekers and refugees coexists alongside its policy of indefinite detention in offshore centres for asylum seekers arriving by sea, and government and media discourse that vilifies asylum seekers and feeds anti-asylum seeker sentiments (Augoustinos and Quinn 2003; Pedersen et al 2006;Every and Augoustinos 2007;McKay et al 2012, Trounson et al 2015. Our anticipation is that these contradictory political discourses and the demographic realities will be reflected in contradictory attitudes on Australian multiculturalism.…”
Section: Introductionmentioning
confidence: 99%
“…Such increases in racist incidents have coincided with a (failed) political attempt to amend/repeal Section 18C of the Racial Discrimination Act-a legislative protection from 'offensive behaviour because of race, colour or national or ethnic origin' (Racial Discrimination Act 1975, s.18C). Australia's formal humanitarian intake of asylum seekers and refugees coexists alongside its policy of indefinite detention in offshore centres for asylum seekers arriving by sea, and government and media discourse that vilifies asylum seekers and feeds anti-asylum seeker sentiments (Augoustinos and Quinn 2003; Pedersen et al 2006;Every and Augoustinos 2007;McKay et al 2012, Trounson et al 2015. Our anticipation is that these contradictory political discourses and the demographic realities will be reflected in contradictory attitudes on Australian multiculturalism.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, the vast majority of participants reported a lack of accurate knowledge about asylum seekers and asylum-seeker issues; interestingly, the knowledge that participants did have corresponded with media reporting on the issue (McKay et al, 2012). This brings us to our next point -the role of the media in the reporting of false beliefs.…”
Section: False Beliefs About Asylum Seekersmentioning
confidence: 89%
“…Thus, asylum seekers are considered as 'undocumented immigrants'; they have no access to basic human rights such as work rights, education, or healthcare, and are constantly vulnerable to being arrested and indefinitely detained by authorities (Mathew & Harley, 2014). Such false beliefs continue to be a common fixture in the discourse surrounding asylum seekers (McKay, Thomas, & Kneebone, 2012;Sulaiman-Hill, Thompson, Afsar, & Hodliffe, 2011). It is beyond the scope of this article to outline all false beliefs about asylum seekers to Australia.…”
Section: False Beliefs About Asylum Seekersmentioning
confidence: 97%
See 1 more Smart Citation
“…While an annual quota is set by the Australian Government for this component, since 1996 a link has been made between the onshore and offshore components. This means that an increase in visa numbers granted to people found to be refugees who arrived onshore results in a decreased number of visas offered to offshore refugees (McKay, Thomas, & Kneebone 2012).…”
Section: Policy Overviewmentioning
confidence: 99%